Clinical feasibility of a new method to identify chronotropic incompetence in heart failure patients. (7th October 2016) - Li, Hui; Li, Jingbo; Zhou, Xiaohong; Zhao, Jianrong; Zhang, Fengru; Wu, Liqun; Shen, Hong; Wan, Qing; Huang, Jing; Yang, Shungang; Wang, Ping
Abstract: Heart failure patients have a high incidence of chronotropic incompetence (CI) that receives less clinical attention. This study assessed a method using wearable devices to identify CI in heart failure patients. Twenty-six heart failure patients (LVEF: 43.9 ± 5.7% with LVEF ⩾40% in 19 patients; age: 52.8 ± 12.4 years, female patients = 6) were enrolled. Each patient underwent symptom-limited treadmill maximal exercise testing during which the simultaneous recording of ECG Holter and physical activity using Actigraph was conducted. The APMHR ratio, the maximal heart rate during peak exercise over the age-predicted maximal heart rate (APMHR, 220-age), was determined. CI was diagnosed in patients who failed to reach at least 0.70 APMHR ratio. Holter-Actigraph recording was also applied during a 6 min hall walk (6MHW) and for 24 h to validate the method to assess impaired chronotropic response. Based on the reports of exercise testing in 26 patients, 13 patients (50%) failed to reach at least 0.70 APMHR ratio while the remaining 13 patients achieved ⩾0.70 APMHR ratio. The APMHR ratio measured by Holter-Actigraph recording was significantly correlated with the APMHR ratio based on exercise test reports ( R = 0.99, P < 0.001). The cut-off values of APMHR ratio (0.65) measured during 6MHW, APMHR ratio (0.69) measured during daily activities, and maximum Δ heart rate (37.8 bpm) measured during daily activities significantly predicted the results of exercise test reports with an area under the ROC curve of 0.7337, 0.7544 and 0.7870, respectively (all P values < 0.05). This pilot study found that the wearable device can potentially help in the identification of chronotropic incompetence in heart failure patients.